FINDING HYPOPHOSPHASIA. LOW LEVEL OF ALKALINE PHOSPHATASE PATIENTS SCREENING - A. V. Vitebskaya (Медицинский совет, 2017)
Study objectives: To conduct screening of alkaline phosphatase (ALP) levels; compare the frequency of detection of low ALP levels using different diagnostic systems; evaluate the possibility of introducing a single «cut-off point». Materials and methods: We analyzed 5472 ALP tests were from 01.08.2013 to 30.04.2017 (672 tests been done with diagnostic system Synchron (Beckman Coulter), 4800 tests been done with system ADVIA 1800 (Siemens Vista)). Results: Identified 67 (1.2%) tests (55 patients) with low values of ALP: among them 35 patients been treated with glucocorticoids; 4 with cytostatics; the rest patients without therapy (6 were in the debut of juvenile rheumatoid arthritis (3), acute leukemia (1), Kawasaki syndrome (1), erythema nodosum (1), 4 with chronic gastrointestinal diseases, and 3 with mild bronchial asthma , 2 – with infantile cerebral palsy, 1 – with premature sexual development). Low ALP values were detected more often in cases of Beckman Coulter system using (26, 3.87%) than Siemens Vista (45, 0.94%). The sensitivity of the «cut-off point» 150 U/l was 100%, specificity 75.18%; in case of «cut-off point» 100 U/l figures are 56.52% and 88.12%, respectively. Conclusion: low level of alkaline phosphatase is the main biochemical marker of hypophosphatasia; in the study, most cases of ALP reduction were associated with drug administration. Analyzing ALP level it is necessary to use ALP reference values specified by age and gender, as unified «cut-off points» have low specificity and/or sensitivity.